A Computer-Based Environment for Processing and Selection of Seismic Ground Motion Records: OPENSIGNAL - Cimellaro, Gian Paolo; Marasco, Sebastiano (Frontiers in Built Environment, 2015)
A new computer-based platform has been proposed whose novelty consists in modeling the local site effects of the ground motion propagation using a hybrid approach based on an equivalent linear model. The soil behavior is modeled assuming that both the shear modulus and the damping ratio vary with the shear strain amplitude. So the hysteretic behavior of the soil is described using the shear modulus degradation and damping ratio curves. In addition, another originality of the proposed system architecture consists in the evaluation of the Conditional Mean Spectrum (CMS) on the entire Italian territory automatically, knowing the geographical coordinates. The computer-based platform based on signal processing has been developed using a modular programming approach, to enable the selection and the processing of earthquake ground motion records. The proposed computer-based platform combines in unified environment different features such as: (i) selection of ground motion records using both spectral and waveform matching, (ii) signal processing, (iii) response spectra analysis, (iv) soil response analysis etc. The computer-based platform OPENSIGNAL is freely available for the general public at http://areeweb.polito.it/ricerca/ICRED/Software/OpenSignal.php.